Nevus Comedonicus - Niloofar Mehrolhasani (Our Dermatology Online, 2014)
A 51 years old woman was reffered to our dermatology clinic with one year history of numerous skin coloured papuels which gradually worsened with time.phiysical examination revealed that the papules were follicular with 1-2 mm diameter.some papules had dark black keratinous material on their surface, giving them a comedo like appearance (Fig. 1). The lesion were located in right lower quadrant of abdomen.